Modern contraceptive methods knowledge and practice among blind and deaf women in Ethiopia. A cross-sectional survey - Awol Seid Yimer; Lebitsi Maud Modiba (BMC, 2019)
Abstract Background Evidences from various parts of the world reveal that women with disabilities are facing widespread barriers in accessing public services. Service providers and program managers do not grasp the relevance of their work and interventions in addressing the sexual and reproductive health needs of women with disabilities. The present study therefore aimed to assess family planning knowledge and practice among women with sensory disabilities. Methods A mixed method approach using quantitative and qualitative methods was employed to collect the data. The study included 326 blind and deaf women using respondent driven sampling technique and 29 purposely selected key informants. We carried out the study from August 2016-April 2017. The quantitative data were analyzed using SPSS and the qualitative analysis was done using Open code software version 4.02 and triangulated with the quantitative findings. Results The findings showed that nearly two third of the respondents of were sexually active. The majority (97.2%) of study respondents had heard about FP methods, however the level of comprehensive knowledge on modern contraceptive methods was 32.5%. The prevalence of unwanted pregnancy was 67.0% and abortion was 44%. Almost half of sexually active respondents ever used modern contraceptive methods, yet the contraceptive prevalence at the time of survey was 31.1%. Implants were the most commonly used (51%) contraceptive method among current users. Conclusions The use of modern contraceptive methods among women with sensory disabilities was low. Thus, the government and concerned organizations need to address the attitudinal, social, and physical barriers women with sensory disabilities are facing while seeking, accessing to and using family planning services.